PENGARUH KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA GURU DIMODERASI GAYA KEPEMIMPINAN TRANSFORMASIONAL ( Studi Kasus Guru Sekolah Dasar UPT Dinas Pendidikan Kecamatan Pamotan Kabupaten Rembang ) - Muhammad Kafit, 13.52.02.0078; Fauzan, Muhamad (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of organizational commitment and motivation on the performance of teachers who moderated transformational leadership style. The population in this study is a civil servant teachers throughout the District Pamotan SD Rembang. This study uses a sampling technique with the number of respondents 132 people. Data were collected using aquestionnaire and processed using SPSS. The results show the organizations commitment significant negative effect on teacher performance, motivation does not affect the performance of teachers, transformational leadership style have a significant effect on the performance of teachers, transformational leadership style moderate the organizationscommitment to teacher performance, and transformational leadership style did not moderate the motivation of the teachers performance. Keywords: organizational commitment, motivation, transformational leadership and teacher performance.